Epstein–Barr virus reactivation influences clonal evolution in human herpesvirus‐8‐related lymphoproliferative disorders. Issue 6 (4th October 2021) - Granai, Massimo; Facchetti, Mattia; Mancini, Virginia; Goedhals, Jacqueline; Sherriff, Alicia; Mundo, Lucia; Bellan, Cristiana; Amato, Teresa; Sorrentino, Ester; Ungari, Marco; Raphael, Martine; Leoncini, Lorenzo; et al.
Abstract : Background: Human herpesvirus‐8 (HHV8) is a lymphotropic virus associated with different lymphoproliferative disorders, including primary effusion lymphoma (PEL), multicentric Castleman's disease (MCD), diffuse large B‐cell lymphomas, not otherwise specified, and the rare entity known as germinotropic lymphoproliferative disorder (GLPD). In PELs and GLPD the neoplastic cells also contain Epstein–Barr virus (EBV). In addition, occasional cases with atypical and overlapping features among these entities have been recognised, suggesting that the spectrum of the HHV8‐related lesions may not be fully characterised. Aims: Here, we report two cases of lymphoproliferative disorder associated with HHV8 and EBV that further expand the spectrum of HHV8/EBV‐positive lymphoproliferative disease. Methods and results: Case 1 represented HHV8/EBV‐positive extracavitary nodal PEL followed by pleural PEL. The striking characteristic of this case was the almost focal and intrasinusoidal localisation of the neoplastic cells and the association with Castleman's disease features. In the second case, we found the entire spectrum of HHV8‐related disorders, i.e. MCD, GLPD, and PEL, coexisting in the same lymph node, underlining the variability, possible overlap and evolution among these entities. Both cases were well analysed with immunohistochemistry, determination of the EBV latency programme, and molecular analysis for clonality of immnoglobulin genes. In both patients, the disease followed an unexpected indolent course, both being still alive after 8 and 12 months, respectively. Conclusion: Our findings represent further evidence of the overlap among HHV8/EBV‐positive lymphoproliferative disorders, and underline a grey zone that requires further study; they further confirm the experimental evidence that lytic EBV replication influences HHV8‐related tumorigenesis.